Blue Economics in Islamic Economics Perspective: Fiqh Bi’ah Approach: Fiqh Bi’ah Approach - Citaningati, Putri Rizka; Alfianto, Tri (Universitas Muhammadiyah Surakarta, 2024)
This research explores the implementation of the blue economy in various Islamic countries, focusing on marine resource production and environmental conservation efforts. Conceptually, the blue economy aligns with the principles of fiqh bi'ah, which emphasize preserving natural resources while ensuring their sustainable use. The study employs an exploratory qualitative approach, using a comprehensive literature review of sources from predominantly Muslim countries such as Indonesia, Pakistan, Bangladesh, Iran, and the Maldives. Sources were selected based on their relevance to blue economy practices, Islamic environmental ethics, and sustainable development in fisheries and aquaculture. The findings indicate that the fisheries sector significantly contributes to economic growth but needs to be balanced with marine ecosystem conservation. Both capture fisheries and aquaculture production have the potential to enhance economic growth, while improvements in international fisheries trade are also crucial. By applying the principles of fiqh bi'ah, these countries can balance economic growth while ensuring marine environmental sustainability and compliance with Islamic values. The study concludes that integrating Islamic environmental principles into blue economy strategies can support long-term sustainability while fostering economic resilience.